2018
DOI: 10.1371/journal.pone.0198448
|View full text |Cite
|
Sign up to set email alerts
|

Metabolome disruption of pregnant rats and their offspring resulting from repeated exposure to a pesticide mixture representative of environmental contamination in Brittany

Abstract: The use of pesticides exposes humans to numerous harmful molecules. Exposure in early-life may be responsible for adverse effects in later life. This study aimed to assess the metabolic modifications induced in pregnant rats and their offspring by a pesticide mixture representative of human exposure. Ten pregnant rats were exposed to a mixture of eight pesticides: acetochlor (246 μg/kg bw/d) + bromoxynil (12 μg/kg bw/d) + carbofuran (22.5 μg/kg bw/d) + chlormequat (35 μg/kg bw/d) + ethephon (22.5 μg/kg bw/d) +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 63 publications
1
26
0
Order By: Relevance
“…59,60 Metabolomics and proteomic studies reported signs of liver dysfunction and hepatic lipid accumulation in adult 61 and in pregnant rats. 62 Another group also suggested a fatty liver condition development in female rats with a long-term exposure of Roundup, 32 based on a multi-omics study. The present study adds to the current understanding of the adverse effects of herbicides on liver and adipose tissues by reporting an increase in inflammation and fibrosis of liver with a subacute exposure of Roundup.…”
Section: Discussionmentioning
confidence: 99%
“…59,60 Metabolomics and proteomic studies reported signs of liver dysfunction and hepatic lipid accumulation in adult 61 and in pregnant rats. 62 Another group also suggested a fatty liver condition development in female rats with a long-term exposure of Roundup, 32 based on a multi-omics study. The present study adds to the current understanding of the adverse effects of herbicides on liver and adipose tissues by reporting an increase in inflammation and fibrosis of liver with a subacute exposure of Roundup.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is hypothesised that the effects of glyphosate in the brain might be linked to glutamate excitotoxicity and oxidative stress, the molecular target(s) of glyphosate in the brain is/are not well defined. As introduced above, glyphosate is best known for its direct inhibitory effects on EPSPS.…”
Section: Introductionmentioning
confidence: 99%
“…This is important because a few studies suggest that some of the observed adverse effects of GBH are not triggered by glyphosate itself but by some adjuvants, or 'inert' molecules, found in the pesticide formulation, such as the polyethoxylated tallowamine. 41,42 Although it is hypothesised that the effects of glyphosate in the brain might be linked to glutamate excitotoxicity and oxidative stress, 21,26,38,43 the molecular target(s) of glyphosate in the brain is/are not well defined. As introduced above, glyphosate is best known for its direct inhibitory effects on EPSPS.…”
mentioning
confidence: 99%
“…Fatty acids, like arachidonic acid, oleic acid, docosahexaenoic acid, and linoleic acid, were downregulated from 24-h through 14-days. Several studies of long-term, low-dose exposures to OPs have shown similar metabolic results indicating a dysfunction in glycolysis/TCA cycle and a shift toward beta-oxidation of fatty acids as a response (Bonvallot 2018 ; Wang 2009 ; Zhang 2010 ). Studies performed by Wang et al investigating serum metabolic profiles of rats exposed to low doses of chlorpyrifos showed decreases in serum lactate levels, which was seen in our study, and a decrease in very low-density lipids (VLDL) (Wang 2009 ).…”
Section: Resultsmentioning
confidence: 88%